Design of abiotic polymer ligand-decorated lipid nanoparticles for effective neutralization of target toxins in the blood. (9th July 2021) - Koide, Hiroyuki; Yamauchi, Ikumi; Hoshino, Yu; Yasuno, Go; Okamoto, Takumi; Akashi, Sotaro; Saito, Kazuhiro; Oku, Naoto; Asai, Tomohiro
Abstract : We developed abiotic polymer ligand (PL)-decorated lipid nanoparticles (LNPs) to improve PL mobility, decrease aggregation after capturing the target, and increase the blood circulation time to achieve highly effective toxin neutralization in vivo . Abstract : Macromolecular toxins often induce inflammatory cytokine production, multiple-organ dysfunction, and cell death. Synthetic polymer ligands (PLs) prepared with several functional monomers have the potential of neutralizing target toxins after binding to them; therefore, they are of significant interest as abiotic antidotes. Although PLs show little toxin neutralization effect in the bloodstream because of immediate elimination from there, the toxin neutralization effect is significantly improved by the direct decoration of PLs onto lipid nanoparticles (PL-LNPs). However, this direct decoration decreases PL mobility, induces LNP aggregation after capturing the target, and decreases LNP blood circulation time. We designed novel PL-LNPs to improve PL mobility, inhibit the aggregation tendency after capturing the target, and increase LNP blood circulation time in order to achieve highly effective toxin neutralization in vivo . Specifically, LNPs were modified with PLs-conjugated polyethylene glycol (PEG), and additional PEG was used to modify the PL-decorated LNPs (PL-PEG-LNPs). Histones were used as target toxins, and N -isopropylacrylamide-based PLs were used for histone capture. PEGylation increased the plasma LNP level 24 h after intravenous injection by ∼90 times and inhibited LNP aggregation after histone capture. The dissociation constant ( K d ) of PL-PEG-LNPs against histone was two times smaller compared to that of PL-LNPs. Although PL-LNPs inhibited histone–platelet interaction in the bloodstream, a large amount of histone–PL-LNP complexes accumulated in the lungs because of aggregation. However, PL-PEG-LNPs inhibited both histone–platelet interaction and histone accumulation in the lungs. Importantly, PL-PEG-LNP treatment increased the survival rate of histone-treated mice compared to PL-LNPs. These results provide a platform for the development of abiotic antidote nanoparticles in vivo .